Determination of posterolateral oropharyngeal wall thickness and the potential implications for transoral surgical margins in tonsil cancer. Issue 7 (29th March 2021) - Tomblinson, Courtney M.; Fletcher, Geoffrey P.; Hu, Leland S.; Mi, Lanyu; Howard, Brittany E.; Nagel, Thomas H.; Hinni, Michael L.; Hoxworth, Joseph M.
Abstract: Background: Margins in transoral surgery for tonsil cancer can be limited by oropharyngeal wall thickness (OWT), but the normal range is not well established. Methods: In 240 noncancer subjects, OWT was measured bilaterally in the vicinity of the tonsils with MRI. Statistical analysis was performed to assess for interaction of age, sex, location, and obesity. Results: Mean(SD) OWT measured 3.4(0.6) mm posteriorly, 3.7(2.0) mm between the styloglossus and stylopharyngeus, and 5.3(0.8) mm laterally. OWT was greater in men, correlated with obesity, decreased posteriorly and laterally in the 60–80 versus 40–59 year age groups, and increased when styloglossus/stylopharyngeus were closer. OWT was <5 mm in 36.7%–97.9% of locations, with the largest percentage below this threshold located posteriorly. Conclusions: OWT is frequently <5 mm, particularly in the posterior and intermuscular areas, suggesting that a smaller surgical margin may need to be accepted in transoral tonsil cancer surgery for anatomic reasons.